Nondestructive Analysis of Silver Coins Minted in Taras (South Italy) between the V and the III Centuries BC. (6th June 2014) - Buccolieri, Alessandro; Buccolieri, Giovanni; Filippo, Emanuela; Manno, Daniela; Sarcinelli, Giuseppe; Siciliano, Aldo; Vitale, Rosa; Serra, Antonio
Abstract : This work enters in an interdisciplinary research project involving the archaeometrical analysis of ancient silver coins minted in the Greek colony of Taras (the modern south Italian town of Taranto) between the V century BC and the III century BC. In this work, by comparing the results obtained from X-ray microanalysis data acquired from the least corroded surface areas and the cross-section of coins from SEM-EDX and from XRF analysis, we have demonstrated that analysed coins exhibited a corrosion layer no more than 25  μ m and that surface silver enrichment was less than 1 wt%. Thus, the data obtained by using X-ray microanalysis from surface may not significantly differ from the original bulk composition. Our results demonstrate that the silver content in the coins decreases considerably ranging from about 97% for the older down to 80% for the ones of 3rd Evans period (300–270 BC), corresponding to the significant social change in the period.